Tumor calcification as a prognostic factor in cetuximab plus chemotherapy-treated patients with metastatic colorectal cancer. Issue 2 (February 2019) - Zhou, Yuwen; Zhang, Jing; Dan Pu,; Bi, Feng; Chen, Ye; Liu, Jiyan; Li, Qiu; Gou, Hongfeng; Wu, Bing; Qiu, Meng
Abstract : This study aimed to explore the correlation between survival and tumor calcification in patients with metastatic colorectal cancer who received cetuximab combined with chemotherapy. The study was a single-center retrospective analysis that enrolled 111 patients who had received therapy between April 2011 and October 2016. Tumor calcification and treatment efficacy were evaluated independently by radiologists on the basis of computed tomography scans. Clinical characteristics and follow-up data were collected from electronic medical records. Correlations between tumor calcification and clinical characteristics, tumor response rate, and patient survival were analyzed. Among the 111 enrolled patients, 27 had tumor calcification [27/111 (24.3%)]. The median progression-free survival was significantly longer for patients with tumor calcification than for those without calcification (9.3 vs. 6.2 months, P =0.022). Patients with tumor calcification also had a higher objective response rate (55.6 vs. 31%, P =0.021) and better overall survival (21.9 vs. 16.5 months, P =0.084). The correlation between calcification features and prognosis showed that patients with an increasing number of calcifications after treatment had a significantly longer median overall survival (22.9 vs. 9.1 months, P =0.033). Simultaneously, new liver metastases and multiple calcifications also showed a trend toward better overall survival. There were also no significant correlations between clinical characteristics (sex, age, gene mutation, primary tumor location, pathological type, blood test result) and survival (Supplementary Table 1, Supplemental digital content 1, http://links.lww.com/ACD/A280 ). Tumor calcification is associated with a better treatment outcome and is a potential prognostic marker. Abstract : Supplemental Digital Content is available in the text.